2022
DOI: 10.1021/acs.iecr.1c04321
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Process Design for Acetone Purification Produced via Dehydrogenation of 2-Propanol

Abstract: Acetone purification is one of the most critical stages of its production process, because a large amount of energy is required. Due to this high energy consumption, the process turns out to be not very sustainable and not friendly to the environment. In this sense, the development of intensified alternatives that minimize energy consumption in this process is of utmost importance. Besides, the safest possible processes are sought, so it is necessary that the control properties of these novel processes be stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…13 The same indicators also were employed by Amezquita-Ortiz et al for assessing the energy-intensified TC and Petlyuk configurations for the purification of acetone. 14 González-Navarrete et al investigated on the application of process intensification such as TC, DWC, and Petyluk, applied to the reactive distillation (RD) for sustainable purification of lactic acid, focusing on the economic viability, environmental impact, and inherent safety as the three main sustainability indicators. 15 Bravo-García et al compared the sustainability of energyintensified TC and DWC for the recovery of valuable components from nylon industry effluents based on similar green metrics such as economics, environmental emissions, safety, and dynamic controllability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The same indicators also were employed by Amezquita-Ortiz et al for assessing the energy-intensified TC and Petlyuk configurations for the purification of acetone. 14 González-Navarrete et al investigated on the application of process intensification such as TC, DWC, and Petyluk, applied to the reactive distillation (RD) for sustainable purification of lactic acid, focusing on the economic viability, environmental impact, and inherent safety as the three main sustainability indicators. 15 Bravo-García et al compared the sustainability of energyintensified TC and DWC for the recovery of valuable components from nylon industry effluents based on similar green metrics such as economics, environmental emissions, safety, and dynamic controllability.…”
Section: Introductionmentioning
confidence: 99%
“…The same indicators also were employed by Amezquita‐Ortiz et al . for assessing the energy‐intensified TC and Petlyuk configurations for the purification of acetone 14 . González‐Navarrete et al .…”
Section: Introductionmentioning
confidence: 99%
“…This objective is dependent on the needed recoveries and purities in each product stream, as defined by Eqn. (1).…”
Section: Optimized Designmentioning
confidence: 99%
“…A close interaction between the fundamentals of chemical engineering and current concepts of sustainability in process systems engineering is needed, along with a change in the engineering paradigm towards generating products with a minimal impact on the environment. Today, accounting for the sustainability aspects in the early design stage of intensified processes, such as thermally coupled (TC), 1,2 dividing wall column (DWC), 3,4 and side-stream (SS), 5,6 can help distinguish between processes that are easy or difficult to operate. 7 To achieve this, Jiménez-González et al suggested the additional consideration of different 'green metrics', such as environmental, safety, and process control, when designing an intensified process, with aim of achieving a wider goal of environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation